Learn by Doing: Boilermakers Succeed with Experiential Education - Parker Ginter, Daniel; Doninger, Katy; Stremiecki, Kathryn; Dobbs-Oates, Jennifer (Experiential Learning and Teaching in Higher Education, 2025)
Across an enviable range of settings, Purdue University students explain how they benefit from deeply engaging learning experiences.